PENINGKATAN INOVASI DAN KREATIVITAS MELALUI PENDIDIKAN KARAKTER GENERASI Z BERBASIS PESANTREN YANG BERJIWA WIRAUSAHA (STUDI KASUS PADA PONDOK PESANTREN AL-ITTIFAQ) [IMPROVING INNOVATION AND CREATIVITY THROUGH GENERATION Z CHARACTER EDUCATION BASED ON ENTREPRENEURIAL BOARDING SCHOOL (CASE STUDY AT AL-ITTIFAQ BOARDING SCHOOL)] - Kika Nawang Wulan; Dety Mulyanti (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze the integration of character education based on entrepreneurial-minded Islamic boarding schools (pesantren) at Al-Ittifaq Islamic Boarding School and to explore the role of innovation and creativity in achieving national economic stability. The research applies a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that Al-Ittifaq successfully implements character education integrated with entrepreneurial values through practice-based curricula and habitual work ethics. Furthermore, innovations in integrated agriculture, digital entrepreneurship, and creative resource management have significantly fostered an adaptive, independent, and competitive Generation Z. These results highlight that the integration of character and entrepreneurship education within pesantren can serve as an effective strategy for strengthening national economic resilience.